On System of Mixed Fractional Hybrid Differential Equations. (1st June 2022) - Awadalla, Muath; Mahmudov, Nazim I.
Abstract : In this article, we find the necessary conditions for the existence and uniqueness of solutions to a system of hybrid equations that contain mixed fractional derivatives (Caputo and Riemann-Liouville). We also verify the stability of these solutions using the Ulam-Hyers (U-H) technique. Finally, this study ends with applied examples that show how to proceed and verify the conditions of our theoretical results.